If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying K + -7 = -9 Reorder the terms: -7 + K = -9 Solving -7 + K = -9 Solving for variable 'K'. Move all terms containing K to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + K = -9 + 7 Combine like terms: -7 + 7 = 0 0 + K = -9 + 7 K = -9 + 7 Combine like terms: -9 + 7 = -2 K = -2 Simplifying K = -2
| 3(1-2x)=2(5x-1) | | 5x+20=4x+20 | | 14+6=-4(4x-5) | | 4x-12-3x+9=2x+8 | | 2x(x-6)(3x+2)=0 | | 5a^2+3a-2=0 | | -2.3-3x-4.1-x=-3x-0.9 | | ln(3x-6)=8 | | K+12=10 | | K+10=10 | | 3x-2x+8=5x+5+3 | | -2+n=6n+22 | | -3=-15-3x | | 5a-3=a+45 | | M+22=50 | | K+18=36 | | W+39=39 | | K+21=42 | | N+36=36 | | 10x-8+136=180 | | (2d+4)=35 | | K+24=36 | | -6x+21-10=9-10x-8 | | 2x-16+x=2x-12+2 | | X+33=50 | | M+32=40 | | 7x/14x | | M+12=12 | | 1.75x+1.50y=337.50 | | 4/3x=90 | | 29(v-990)=-232 | | x^4=0.207 |